Large area growth of ZnO nanorod arrays on the stainless steel grid by aqueous solutions. (10th November 2017) - Zhao, Yucheng; Yu, Naisen; Dong, Ximeng; Yan, Han
Abstract: Large-area ZnO nanorod arrays have been synthesised on a stainless steel grid by two-step growth approach, including the synthesis of seed layer and growth of ZnO nanorods in aqueous solution. X-ray diffraction analysis and energy dispersive X-ray elemental mapping measurements indicate wurtzite ZnO structures are formed. Scanning electron microscopy shows high uniform coverage of the densely packed ZnO nanorod arrays are grown on the stainless steel grid frame, and the as-grown ZnO nanorods have uniform diameters. Meanwhile, the ZnO nanostructures also show good optical quality and photocatalytic activity. The results show using the stainless steel grid as substrate will provide a promising way of producing large-scale nanorod arrays with good controllability and morphologies. And it will be critical in potential application such as high-efficiency filtering and catalysts.